Genetic Parameters of Agronomic Traits in Sweetpotato Accessions - Rahajeng, Wiwit; Restuono, Joko; Indriani, Febria Cahya; Purwono, Purwono (Department of Biology, Faculty of Mathematics and Sciences, Semarang State University . Ro, 2020)
Germplasm as a source of genes in sweetpotato breeding requires information on appearance and genetic parameters. The objectives of this research were to determine the performance and genetic parameters of sweet potato accessions. The research was conducted at Kendalpayak Research Station, Malang, East Java, Indonesia. The materials used were thirty sweet potato accessions from Indonesian Legumes and Tuber Crops Research Institute (ILETRI) germplasm collection. The research was arranged in a Randomized Block Design (RBD) with two replications. The variables observed included: the vines length, the weight of vines, the number and weight of the saleable root per plot, the number and weight of the non-saleable root per plot, the number and weight of root per plant, the root yield, the harvest index, and the dry matter content. The results of ANOVA showed a significant difference among the tested genotypes in almost all traits observed except on weight of non-saleable root. PCV estimation was higher than GCV estimation for all the observed characters. The weight of the saleable root per plot, the weight of root per plant, and the root yield that showed a wide range of PCV and GCV as well as high broad-sense heritability indicated that these traits had additive gene effect and more reliable for effective selection. The broad GCV in a population is effective for selection to obtain the superior variety.